PA 02-2-1573 Lack of association between country-specific publications indexed in medline and violence-related mortality: the need for research capacity building. (November 2018) - Salmi, Louis-Rachid; Bailhache, Marion
Abstract : Context and objective: The World Health Organization (WHO) recommends that countries base their injury prevention strategies on context-specific research. To test the hypothesis that this recommendation is not respected, we estimated whether publications on violence were associated with the burden of violence-related mortality or with income level and research capacity of countries. Methods: We identified in PubMed/Medline all documents for which the Medical Subject Heading was 'violence', and the country of authors, using the 'AD' identifier. We identified countries in the World Bank database on Countries and Economies, and mortality data in the 2014 WHO global report on violence prevention. Countries were classified, based on their Gross National Income (GNI, World Bank), as Low-, Middle-, or High-Income level (LIC, MIC, HIC). Research capacity was defined by the number of Higher Education Institutions (HEIs), from the Webometrics Ranking of World HEIs (Cybermetrics Lab, Spain). Correlation between publications and mortality, GNI and HEIs per population was estimated. Median numbers of publications by regions or income groups were compared. Results: Of 180 countries with full information, 31 (17.2%) had no publication on violence with authors based in the country. The median number of violence-related publications by country was 8 (Inter Quartile Interval [IQI] 2–59), and the maximum was 25 445 (USA); the median number of publications varied from 1 in Oceania to 23 in Europe (p<0.0001). The number of publications was not correlated with violence-related mortality (r=−0.032; NS), but with the GNI (r=0.257; p<0.05), the number of HEIs per population (r=0.262; p<0.05). It was higher in HIC (median: 75; IQI: 9–453) than in MIC (4; IQI: 1–20) and LIC (7; IQI: 2–18). Conclusion: Many countries might not be basing violence prevention on country-specific published research. The association with GNI and with HIE suggests a priority to build countries' capacity to develop research on violence.